A Carta de 25 de Fevereiro de 1327 e a Norma dita de 18 de Fevereiro de 1332 - Jorge Manuel de Matos Pina Martins Prata (Medievalista)
A letter written by Gonçalo Domingues under royal command (Estremoz, February 25th 1327) has been considered by portuguese historians as an ordenamento (ordinance) forbidding lawyers and attorneys to be in residence in the royal Court tribunals.However, the internal analysis of the said letter, and its comparison with other charters of undisputed normative nature, as well as with the ordinance commonly accepted as having been issued on February 18th 1332, in Estremoz, allow us to infer that the mentioned 1327 letter is an introductory note whose primordial purpose was to accompany and introduce the ordinance of February 18th 1332, in its diffusion throughout the Kingdom: this leads to the conclusion that the allegedelly 1332 ordinance was in fact enacted in 1327. Thus, we can establish the documental production stages of the Ordenação sobre o Livramento dos feitos na Corte e proibição de advogados e procuradores residentes na Corte (Ordinance on the King´s Court Judicial Procedures and Prohibition of Lawyers and Attorneys to be in residence in the Court): such ordinance was enacted on February 18th 1327, in Estremoz; some days later, on February 25th of that same year, it would be sent throughout the Kingdom with the letter written, that same day and place, by Gonçalo Domingues under command of D. Afonso IV. In fact, on March 6th 1327, in accordance with its own stipulations, it was proclaimed in Arraiolos, as we know from the Foros de Beja.